At the abyss : an insider's history of the Cold War - Reed, Thomas C.; Bush, George, 1924- (New York : Presidio Press/Ballantine Books, 2004)
An unvarnished view of America's fight against Communism, from the end of WWII to the closing of the Strategic Air Command.
Communist takeovers and makeovers -- The fifties unfold -- The Paparazzi pilots -- Howard Hughes supplies the props -- Rockets and missiles -- Sputnik and the missile gap -- Nuclear weapons and the Soviet Union -- The American cyberskippers -- The resumption of nuclear tests -- Getting started in Vietnam -- Winter on the Spanish coast -- Dawn of the information age -- The Air Force recovers from Vietnam -- Inefficiency kills, empires as well as people -- President Reagan sets up the checkmate -- Ghost stories from the Reagan White House -- The queen of hearts -- Cheney, Powell, and the nuclear genie -- The closers -- The Soviet solstice -- The heroes -- Closing down.
Introduction by George H.W. Bush.
"A Presidio Press book." ; Ballantine Books.
Includes bibliographucal references and index.
Keywords: Cold War; World politics -- 1945-1989.; United States -- Foreign relations -- Soviet Union; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- 1945-1989.; United States -- Politics and government -- 1945-1989.